COMMUNICATION ANNOYANCE AMONG POLYTECHNIC STUDENTS - KARSAHID, HAZARIAH; ABU BAKAR, FAIZATUL ABSHARIZAN; AHMAD SARKAWI, AZNURULLAILI (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2023)
Communication Annoyance Among Polytechnic Students Hazariah Karsahid1, Faizatul Absharizan binti Abu Bakar2, Aznurullaili Binti Ahmad Sarkawi3 Jabatan Perdagangan, Politeknik Sultan Azlan Shah Behrang Stesyen, 35950 Behrang, Perak Email : ijasahid73@gmail.com ABSTRACT In the day-to-day process, the ability to communicate effectively is crucial. A good student should be willing to examine himself in order to be aware of his level of deprivation and to strive to improve over time. This is because, according to a Malaysian Government study of graduates, around 60,000 graduates have yet to be approved for employment, and one of the causes for this difficulty is graduates' lack of communication skills. As a result, the objectives of this study are to (i) identify the level of difference in students' annoyance, whether caused by verbal or nonverbal communication; (ii) assess the difference in communication irritation between male and female students; and (iii) identify the communication situation in which students are most annoyed, whether in terms of group discussion, meeting, interpersonal interaction, public speaking, or writing. Random sampling was used to distribute 143 questionnaires to Polytechnic Sultan Azlan Shah students. According to the data, there was no significant difference in students' frustration levels between verbal and non-verbal communication. Furthermore, there was no statistically significant difference between male and female students in terms of communication annoyance. The findings then show that public speaking is the type of communication that students dread the most. This study's findings can be used by all lecturers and institutions to create the greatest types of education and program for supporting and encouraging students' talents to talk effectively, confidently, and courageously. Keywords: Communication, public speaking, non-verbal, verbal, writing